First synthesis of nitrosporeusines, alkaloids with multiple biological activities - Philkhana, Satish Chandra; Jachak, Gorakhnath R.; Gunjal, Vidya B.; Dhage, Nagsen M.; Bansode, Ajay H.; Reddy, D. Srinivasa (Tetrahedron Letters, 2015)
Synthesis of nitrosporeusines A and B, thioester-bearing alkaloids from the Arctic Streptomyces nitrosporeus with exceptional biological activity is disclosed for the first time. In addition, we have prepared another biologically important natural product, maleimycin, in optically pure form using a gram-scale enzymatic resolution method. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Enzymatic resolution; Influenza H1N1 virus; Maleimycin; Michael reaction; Nitrosporeusine

Solution-phase synthesis of the macrocyclic core of teixobactin - Dhara, Santu; Gunjal, Vidya B.; Handore, Kishor L.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2016)
Towards the total chemical synthesis of the exceptionally potent antibiotic teixobactin, we synthesized the macrocyclic core of a natural product by using a solution-phase approach. The gramscale synthesis of L-allo-enduracididine and Shiina macrolactonization are highlights of the present disclosure.

Synthetic studies towards Pseudoxylallemycin B, an antibiotic active against gram-negative bacteria: total synthesis of 3-epi-Pseudoxylallemycin B - Gunjal, Vidya B. (Tetrahedron Letters, 2018)
In an attempt towards the total synthesis of Pseudoxylallemycin B, a homo dimeric, N-methylated macrocyclic tetrapeptidic natural product, synthesis of its epimer at position 3 (d-Tyr instead of l-Tyr) is described here. During the course of synthesis we came across a striking yet unusual observation of complete epimerization which led to the formation of 3-epi-Pseudoxylallemycin B.
Keywords: Cyclic tetrapeptides; Epimerization; Gram-negative bacteria; Macrolactamization; Propyl phosphonic anhydride (T3P)

Total synthesis of Met(10)-teixobactin - Gunjal, Vidya B.; Reddy, D. Srinivasa (Tetrahedron Letters, 2019)
The total synthesis of cyclic depsipeptide Met(10)-teixobactin in solution-phase is described. Teixobactin is a structurally and mechanistically novel antimicrobial peptidic natural product with very impressive activities against Gram-positive pathogens. It happens to possess an L-allo-enduracididine (End) residue as part of macrocyclic ring which is not readily accessible. In this report, we have used serine ligation strategy as the key step to prepare an analogue of teixobactin where End being replaced with a readily available amino acid methionine. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: antibiotic; Cyclic tetrapeptides; Serine ligation; Teixobactin

Teixobactin: a paving stone toward a new class of antibiotics? - Gunjal, Vidya B.; Thakare, Ritesh; Chopra, Sidharth; Reddy, D. Srinivasa (Journal of Medicinal Chemistry, 2020)
Antimicrobial resistance is a serious threat to human health worldwide, prompting research efforts on a massive scale in search of novel antibiotics to fill an urgent need for a remedy. Teixobactin, a macrocyclic depsipeptide natural product, isolated from uncultured bacteria (Elef theria terrae), displayed potent activity against several Gram-positive pathogenic bacteria. The distinct pharmacological profile and interesting structural features of teixobactin with nonstandard amino acid (three Damino acids and L-allo-enduracididine) residues attracted several research groups to work on this target molecule in search of novel antibiotics with new mechanism. Herein, we present a comprehensive and critical perspective on immense possibilities offered by teixobactin in the domain of drug discovery. Efforts made by various research groups since its isolation are discussed, highlighting the molecule's considerable potential with special emphasis on replacement of amino acids. Critical analysis of synthetic efforts, SAR studies, and the way forward are provided hereunder.